2013
DOI: 10.1371/journal.pgen.1003784
|View full text |Cite
|
Sign up to set email alerts
|

MEIOB Targets Single-Strand DNA and Is Necessary for Meiotic Recombination

Abstract: Meiotic recombination is a mandatory process for sexual reproduction. We identified a protein specifically implicated in meiotic homologous recombination that we named: meiosis specific with OB domain (MEIOB). This protein is conserved among metazoan species and contains single-strand DNA binding sites similar to those of RPA1. Our studies in vitro revealed that both recombinant and endogenous MEIOB can be retained on single-strand DNA. Those in vivo demonstrated the specific expression of Meiob in early meiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
142
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(164 citation statements)
references
References 69 publications
(80 reference statements)
15
142
1
6
Order By: Relevance
“…Drosophilia HDM (Hold'em) encodes an OB-fold protein related to RPA70 that is required for a majority of crossover and interacts with the joint-molecule resolving endonuclease complex, MEI9 -ERCC1 -MUS312 (Joyce et al 2009). In mammals, the RPA1-related MEIOB protein and associated factor, SPATA22, form an RPA-associated complex that is required for intermediate steps of recombination and normal synapsis (La Salle et al 2012;Ishishita et al 2013Ishishita et al , 2014Luo et al 2013;Souquet et al 2013). MEIOB -SPATA22 is inferred to act after initial strand exchange, perhaps to promote strand annealing in both SDSA and dHJ pathways, acting analogously to the budding yeast Rad52 protein Luo et al 2013).…”
Section: Recombination-associated Dna Synthesismentioning
confidence: 99%
“…Drosophilia HDM (Hold'em) encodes an OB-fold protein related to RPA70 that is required for a majority of crossover and interacts with the joint-molecule resolving endonuclease complex, MEI9 -ERCC1 -MUS312 (Joyce et al 2009). In mammals, the RPA1-related MEIOB protein and associated factor, SPATA22, form an RPA-associated complex that is required for intermediate steps of recombination and normal synapsis (La Salle et al 2012;Ishishita et al 2013Ishishita et al , 2014Luo et al 2013;Souquet et al 2013). MEIOB -SPATA22 is inferred to act after initial strand exchange, perhaps to promote strand annealing in both SDSA and dHJ pathways, acting analogously to the budding yeast Rad52 protein Luo et al 2013).…”
Section: Recombination-associated Dna Synthesismentioning
confidence: 99%
“…Recently, genetic studies in mice identified two proteins, MEIOB and SPATA22, which are critical for fertility (La Salle et al 2012;Ishishita et al 2013;Luo et al 2013;Souquet et al 2013). MEIOB is of particular interest as it contains a so-called oligonucleotide/oligosaccharide binding (OB) fold, which is common to proteins that bind specifically to tracts of ssDNA, including RPA.…”
Section: Meiob and Spata22mentioning
confidence: 99%
“…MEIOB is of particular interest as it contains a so-called oligonucleotide/oligosaccharide binding (OB) fold, which is common to proteins that bind specifically to tracts of ssDNA, including RPA. Indeed, biochemical experiments show that MEIOB binds ssDNA (Luo et al 2013;Souquet et al 2013). A truncated form of the protein was also found to have ssDNA-specific 3 0 exonuclease activity (Luo et al 2013).…”
Section: Meiob and Spata22mentioning
confidence: 99%
“…Resection is initiated by MRE11-dependent endonucleolytic incisions near DSBs, followed by bidirectional resection that requires both MRN and EXO1 (Zakharyevich et al 2010;Garcia et al 2011 and the 9-1-1 complex are also required to restrain hyperresection (Shinohara et al 2003;Gray et al 2013;Clerici et al 2014). Given that a number of nucleases are involved in the resection process (Mimitou and Symington 2009;Zakharyevich et al 2010;Garcia et al 2011;Schaetzlein et al 2013), an appealing model is that the MCN ensures appropriate resection rates by activating some nucleases, while (temporarily) inhibiting others (Segurado and Diffley 2008;Manfrini et al 2010;Luo et al 2013;Souquet et al 2013). In S. cerevisiae, resection by BLM Sgs1 /DNA2, in particular, is likely only activated late in meiosis (Manfrini et al 2010;Zakharyevich et al 2010).…”
Section: Control Of Dsb Repair Activation Of Dsb End Processingmentioning
confidence: 99%